Perencanaan Sistem Penyaliran Tambang PT. Rajawali Internusa Jobsite PT. Budi Gema Gempita, TJ. Jambu, Merapi Timur, Kabupaten Lahat, Sumatera Selatan - Ekky Maulana Ramadhan Hutapea; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2022)
Abstract. PT.Rajawali Internusa is a mining company engaged in mining contractor, PT.Rajawali Internusa uses the open pit method, therefore water is one of the things that greatly affects production activities. From the results of the analysis of rainfall data in 2011–2020 with a mine opening pit of 11.6Ha, a runoff discharge of 3.403/second was obtained. From drill log data, it can be known the cross section of geology, hydrogeology and fence diagrams as well as the determination of the K value, in terms of the discharge of groundwater entering the Pit by 1.5411/second. It takes a sump to hold water of 409,027.2/day. The total head of the pump that must be provided to drain water as planned is 30,712m, with a pump power of 21,679watts, then the pump needs can be calculated by comparing the runoff volume with the pumping volume with the addition of 5 pumps. Open channel design is known to be the width of the channel base 1m, hydraulic depth 1.5m, the length of the channel slope 1.74m, the topsurface width 2.74m and the channel guard height 0.86m obtained an open channel discharge of 1.186/sec so that it is able to accommodate the pumping water discharge. Keywords: Rainfall, Ground Water, Sump, Pump, Open Channe.